2020
DOI: 10.35308/jlaot.v2i1.2361
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kelimpahan, Komposisi Dan Sumber Sampah Laut: Studi Kasus Pada Pantai Kuala Batu Desa Pulau Kayu Kabupaten Aceh Barat Daya

Abstract: Sampah laut telah menjadi masalah dan ancaman bagi ekosistem, keanekaragaman hayati maupun kehidupan laut. Oleh sebab itu, diperlukan kebijakan, strategi mitigasi dan rencana aksi yang tepat untuk mengatasi masalah tersebut. Tujuan Penelitian ini adalah untuk mendapatkan gambaran tentang jumlah, komposisi dan sumber sampah laut yang nantinya dapat dijadikan referensi untuk mengatasi masalah sampah laut. Penelitian ini dilaksanakan di Pantai Kuala Batu, Desa Pulau Kayu Kabupaten Aceh Barat Daya. Metode pengumpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The high amount of litter on the beach is thought to be due to overlapping activities on the beach, such as tourist attractions and ship docking areas. Rahmayanti et al (2020) found at Kuala Batu Beach, Pulau Kayu Village, Southwest Aceh Regency that most of the marine litter found in this location comes from recreational activities and beach activities. In the South China Sea, it shows that 95% of marine litter found in the area comes from land (land-based sources) through recreational activities and coastal activities as a result of human activities (Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The high amount of litter on the beach is thought to be due to overlapping activities on the beach, such as tourist attractions and ship docking areas. Rahmayanti et al (2020) found at Kuala Batu Beach, Pulau Kayu Village, Southwest Aceh Regency that most of the marine litter found in this location comes from recreational activities and beach activities. In the South China Sea, it shows that 95% of marine litter found in the area comes from land (land-based sources) through recreational activities and coastal activities as a result of human activities (Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 80%
“…About 50% of plastic is buoyant and 60%-64% of the amount of plastic floating in the ocean is estimated to be carried from coastal waters to the high seas (Cózar et al, 2014). Rahmayanti et al (2020) found a high amount of plastic waste with a percentage of 79% at Kuala Batu Beach, West Aceh Regency. The same thing happened along the coastline of NCT Regency, plastic dominated the amount of litter with a percentage of 79,7%.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other types of waste were only obtained at the first and third stations in July and were not obtained in January. Plastic and rubber were also dominant in other locations (Djaguna et al, 2019;Isyrini et al, 2019;Rahmayanti et al, 2020). Observational data for the territory have been more focused on Java Island and big cities.…”
Section: Resultsmentioning
confidence: 99%
“…Research on marine debris in Aceh province on the composition of marine debris has been carried out in West Aceh (Kusumawati et al, 2018;Rahmayanti et al, 2020) and Banda Aceh (Agustina et al, 2020;Nizar et al, 2018a;Ondara & Dhiauddin, 2020), marine debris management (Kusumawati, 2019;Kusumawati & Setyowati, 2020;Nizar et al, 2017), the impact of marine debris on biota (Nufus & Zuriat, 2020), microplastics in Banda Aceh (Yumni et al, 2020) and analysis of debris carbon emissions (Faisal, 2015;Sofriadi et al, 2017). To identify the composition of marine debris in Banda Aceh City, there is only one journal (Agustina et al, 2020) whose research was conducted in river mouths.…”
Section: Introductionmentioning
confidence: 99%